The Effect of Using Different Levels of Thinner Olive Oil (Extra Virgin Olive Oil) on the Viability and Abnormality of Spermatozoa and pH of the Semen Duroc Pigs - Stefanus Nahak; Agustinus Agung Dethan; Paulus Klau Tahuk (Program Studi Peternakan, Fakultas Pertanian Universitas Timor, 2021)
This study aims to determine the effect of using different levels of thinner olive oil (extra virgin olive oil) on the viability and abnormality of spermatozoa and the pH of the semen of duroc pigs. The research took place in September 2020 in Noenebu, Tapenpah Village, Insana District, North Central Timor Regency, and the Laboratory of the Faculty of Agriculture, University of Timor. This study used a completely randomized design (CRD) with 4 treatments and 5 replications. Treatment R1 consist of 10% tris solution, 10% olive oil, 80% semen; R2 treatment consist of 15% tris solution, 15% olive oil, 70% semen; R3 treatment consist of 20% tris solution, 20% olive oil, 60% semen, and R4 treatment consist of 25% tris solution, 25% olive oil, 50% semen. The results showed that the effect of different treatments was very significant (P <0.01) on the viability of spermatozoa. The mean spermatozoa viability of each treatment was R1 of 89 ± 2.57%, R2 of 76.9 ± 12.51%, R3 of 62.8 ± 3.11%, and R4 treatment of 41.2 ± 15, 38%. The spermatozoa abnormalities were significantly different (P <0.05). Where the abnormality of the spermatozoa in treatment R1 was 8.8 ± 1.30%, R2 was 10.4 ± 1.67%, R3 was 11.6 ± 1.81%, and R4 was 14.4 ± 3.78%. The degree of acidity (pH) of the semen was not significantly different between treatments. The pH value of each treatment was R1 of 7.92 ± 0.83, R2 of 8.04 ± 0.54, R3 of 7.96 ± 0.39; and R4 treatment of 8.06 ± 0.64. It can be concluded that the addition of 10% to 20% olive oil can maintain the viability and abnormality of duroc boar male spermatozoa. However, the use of olive oil up to 20% does not affect to degree of acidity of the semen produced.